Material Flow Analysis of Plastic Waste for Circular Economy Potential: A Case Study of Wijaya Kusuma and Sidomakmur Waste Banks in Metro City - Nabila Putriyandri Alifa; Arini Adelia; Aulia Annas Mufti (Publikasi Indonesia, 2024)
The handling of plastic waste remains an ongoing environmental issue in Indonesian municipalities. The aim of this study is to employ Material Flow Analysis (MFA) to assess the efficacy of two central waste banks in Metro City: Bank Sampah Induk (BSI) Wijaya Kusuma and BSI Sidomakmur. The research examines the extent in which these facilities help foster a circular economy and minimize plastic waste by recycling three different forms of plastic: polyethylene terephthalate (PET), high-density polyethylene (HDPE), and polypropylene (PP). Qualitative data was gathered through stakeholder interviews, literature reviews, observations, and close inspection of the processes utilized to treat the collected plastic waste. The study determines both BSI efficacy by comparing the plastic intake and exit flows and figuring out how much garbage is left over after processing.By shredding and recycling into pelletized plastic, BSI Wijaya Kusuma was able to reduce waste by 88.4%, which helped to promote a circular economy. BSI Sidomakmur, on the other hand, showed little technological expertise by employing a compactor resorting to external partnerships to further recycle despite achieving a 96.4% reduction. Even with these facility-level achievements, the aggregate effect of both waste banks only contributes 1.2% to the overall reduction of plastic waste in Metro City. In order to strengthen regional circular economy efforts, this study emphasizes the necessity of more extensive waste bank integration and technology advancements. The results give stakeholders and policymakers important information for enhancing waste management plans and advancing sustainable economic models.